Isolation and characterization of Pseudomonas putida PpF1 mutants defective in the toluene dioxygenase enzyme system. - Finette, B A (1984)
Pseudomonas putida PpF1 degraded toluene via a dihydrodiol pathway to tricarboxylic acid cycle intermediates. The initial reaction was catalyzed by a multicomponent enzyme, toluene dioxygenase, which oxidized toluene to (+)-cis-1(S),2(R)-dihydroxy-3-methylcyclohexa-3,5-diene (cis-toluene dihydrodiol). The enzyme consisted of three protein components: NADH-ferredoxintol oxidoreductase (reductasetol), ferredoxintol, and a terminal oxygenase which is an iron-sulfur protein (ISPtol). Mutants blocked in each of these components were isolated after mutagenesis with nitrosoguanidine. Mutants occurred as colony morphology variants when grown in the presence of toluene on indicator plates containing agar, mineral salts, a growth-supporting nutrient (arginine), 2,3,5-triphenyltetrazolium chloride (TTC), and Nitro Blue Tetrazolium (NBT). Under these conditions, wild-type colonies appeared large and red as a result of TTC reduction. Colonies of reductasetol mutants were white or white with a light blue center, ferredoxintol strains were light blue with a dark blue center, and strains that lacked ISPtol gave dark blue colonies. Blue color differences in the mutant colonies were due to variations in the extent of NBT reduction. Strains lacking all three components appeared white. Toluene dioxygenase mutants were characterized by assaying toluene dioxygenase activity in crude cell extracts which were complemented with purified preparations of each protein component. Between 40 and 60% of the putative mutants selected from the NBT-TTC indicator plates were unable to grow with toluene as the sole source of carbon and energy. This method should prove extremely useful in isolating mutants in other multicomponent oxygenase enzyme systems.